Improvement in left intraventricular pressure gradients after aortic valve replacement in aortic stenosis patients. Issue 4 (20th March 2017) - Guerra, Miguel; Mendes‐Ferreira, Pedro; Adão, Rui; Pereira, Eulália; Vieira, Manuela; Lourenço, André P.; Brás‐Silva, Carmen; Bastos, Pedro; Vouga, Luís; Leite‐Moreira, Adelino F.
Abstract : New Findings: What is the central question of this study? Normal diastolic and systolic intraventricular pressure gradients are decreased when left ventricular filling and/or emptying are compromised. We hypothesized that in patients with severe aortic valve stenosis, a condition that interferes with ventricular filling and emptying, those gradients would be disturbed. What is the main finding and its importance? We showed the existence of intraventricular pressure gradients throughout the cardiac cycle in the human left ventricle. Moreover, we demonstrated, for the first time, that diastolic and systolic gradients, which are markers of normal ventricular filling and emptying, respectively, improved in patients with severe aortic valve stenosis immediately after valve replacement. The present study was conducted to characterize left intraventicular pressure gradients, which are markers of normal cardiac function, in patients with severe aortic stenosis, a condition that interferes with ventricular filling and emptying. In 10 patients (four male; mean age 71.3 ± 4.8 years old) undergoing aortic valve replacement, two high‐fidelity pressure catheters were inserted inside the cavity of the left ventricle through an apical puncture and positioned in the apex and outflow tract below the aortic valve. Pressures were continuously acquired and gradients calculated as apical minus outflow tract pressure, before and immediately after aortic valve replacement. During early filling, we recorded a negative intraventricular gradient along the basal portion of the left ventricle in the apical direction (−0.82 ± 0.45 mmHg), which increased to −3.97 ± 0.42 mmHg after aortic valve replacement. In late filling, intraventricular flow was now directed towards the outflow tract, with a positive pressure gradient both before (+1.23 ± 0.37 mmHg) and after surgery (+2.12 ± 0.58 mmHg). During systole, before surgery we observed a positive pressure gradient between the apex and outflow tract during both rapid (+1.60 ± 0.21 mmHg) and slow ejection phases (+1.68 ± 0.12 mmHg), whereas after aortic valve replacement the positive gradient (+1.54 ± 0.15 mmHg) during rapid ejection was inverted (−3.92 ± 0.34 mmHg) during the slow ejection phase. We demonstrated that in patients with severe aortic stenosis both diastolic and systolic intraventricular pressure gradients are significantly attenuated but can be restored immediately after aortic valve replacement. The assessment and measurement of intraventricular pressure gradients and their modulation in pathophysiological conditions may provide novel insights into cardiac physiology. Abstract :